Ultimate Cardano Smart Contracts: Unlock the Full Potential of the Cardano Blockchain by Developing Real-World Web 3. 0 Projects Using Plutus Smart Contracts, and App Development (English Edition) - Ley, Lawrence Arthur (Orange Education PVT Ltd, 2024)
Unlock the full potential of the Cardano blockchain for building decentralized Web 3.0 apps with Ultimate Cardano Smart Contracts.This book takes you on a journey from the basics of blockchain evolution, cryptography, and Cardano's unique consensus algorithm, to the intricacies of transactions and smart contracts. You'll dive deep into Plutus, Cardano's native smart contract language, and master essential tools like the Transaction Builder and Validators. Learn how to mint your own tokens and utilize the best development tools available.Through a real-world ticketing application project, you'll design, implement, test, and deploy a decentralized application, ensuring robust security and scalability. Troubleshoot common issues and explore the vibrant Cardano ecosystem, filled with resources and communities to support your ongoing development journey.By the end of this book, you'll have the skills and confidence to create sophisticated smart contracts and contribute to the innovative world of Cardano.